Questions of uncertainty in geography. (October 2017) - Fusco, Giovanni; Caglioni, Matteo; Emsellem, Karine; Merad, Myriam; Moreno, Diego; Voiron-Canicio, Christine
The concept of uncertainty has fostered in the last decade's fundamental and applied research in different disciplinary fields.Couclelis (2003) clearly demonstrated the pervasiveness of uncertainty in the production process of geographical knowledge. The paper shares this epistemological point of view. Pragmatically, its goal is to show how questions of uncertainty arise in the praxis of geographic research. It suggests that scientific work can be enriched, and not hindered, by addressing uncertainty in knowledge. The paper discusses eight domains within the activity of the geographer, where questions of uncertainty arise: geographic information, geographic definitions, the explanation of geographic phenomena, the complexity of spatial systems, geosimulation, the representation of spatial knowledge, subjectivity in spatial phenomena, and planning. Within each domain uncertainty issues are identified as well as their possible interrelations.